Effectiveness of ICTs in Dissemination of Agricultural Information among Farmers in Cauvery Delta, Thanjavur - Aarthi Dhakshana Durairajan; Rajandran KVR (International Journal of Supply Chain Management, 2018)
The role of ICT in Agriculture plays a new modern paradigm that facilitates and improves the agricultural sector. The ICT had rendered service to farmers for market access, announcement of weather condition, awareness of crop diseases etc. There are several types of the ICT tools used in agriculture sector such as Radio, Television, Mobile phones, Internet, Electronic money transfer etc. The ICT helps the farmers to understand the gap between productivity and market demand. The ICT, particularly the mobile technology has helped the farm producers in knowing internal commodity prices like agriculture produce. Thus ICT has been a big platform to the farm producer for their empowerment and enhancement. The ICTs assist the farmers to provide and manage the efficient supply chain of the agricultural products. This study attempted to known the impact various ICTs on productivity. The research also determines the factors influencing to refer the ICTs in agriculture. The study focused on to identify the problems faced by the farmers while access the ICTs. The research was conducted in Cauvery Delta Region, Thanjavur District. The data survey collected from 264 respondents by using simple random sampling technique. Regression, Descriptive Statistics and Factor analysis statistical tools were used to evaluate the data. The research findings have provided useful direction for the researcher and Practitioners for to develop future ICT based dissemination systems. Keywords - Agriculture, Awareness, ICT, Farmers, Preference, Retention.